2019
DOI: 10.1002/jcsm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a physical activity programme to prevent physical performance decline in onco‐geriatric patients: a randomized multicentre trial

Abstract: Background Older adults with cancer experience negative long‐term functional effects of both cancer and treatments. Exercise may minimize their age‐related and cancer‐related functional decline. Methods We conducted a multicentre open‐label 12 month randomized clinical trial with two parallel arms including participants aged ≥70 years with lymphoma or carcinoma requiring curative treatment. The study started at the beginning of any phase of cancer treatment (surgery, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(118 citation statements)
references
References 43 publications
(84 reference statements)
0
116
0
2
Order By: Relevance
“…Studies have suggested that interventions employing only aerobic exercise have been less successful in maintaining muscle mass in older cancer survivors. For example, a French study randomized 301 cancer patients over the age of 70 who were initiating treatment (surgery, chemotherapy or radiation) to a 12-month telephone-based aerobic physical activity intervention or usual care control ( 115 ). After 1 year, there was no difference in SPPB scores between groups (P=0.772).…”
Section: Physical Activity Muscle Mass and Functional Status In Oldmentioning
confidence: 99%
“…Studies have suggested that interventions employing only aerobic exercise have been less successful in maintaining muscle mass in older cancer survivors. For example, a French study randomized 301 cancer patients over the age of 70 who were initiating treatment (surgery, chemotherapy or radiation) to a 12-month telephone-based aerobic physical activity intervention or usual care control ( 115 ). After 1 year, there was no difference in SPPB scores between groups (P=0.772).…”
Section: Physical Activity Muscle Mass and Functional Status In Oldmentioning
confidence: 99%
“…The design and setup of the included studies are summarized in Table 1 . The studies were conducted in France [ 30 ], Canada [ 31 ], USA [ 32 ], and Japan [ 33 ], and published from 2014 to 2019. The studies were all RCTs, however, one study was a pilot RCT [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies excluded patients who were already physically active [ 31 , 32 ], and two excluded patients with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) > 1 [ 33 ] and > 2 [ 30 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size calculation was performed with nQuery Advisor V7.0. From the literature, [ 64 71 ] the cut-off values for the primary endpoint were selected such that in each component, an incidence of 10% to 15% is expected over 3 years. Depending on the correlation of the events, this may lead to a proportion of event-free patients of about 27% to 80% at the end of the observation period.…”
Section: Methods: Data Collection Management and Analysismentioning
confidence: 99%